(untitled) (World Science, 2020)
The article considers the contribution to Ukrainian in the music of the late 19th - early 20th centuries of the poet, public figure, researcher Ivan Franko. Advocating Western Ukrainian folklore, the poet turned to journalism and music criticism. Ukrainian composers created romances, choirs, cantatas, oratorios, vocal-symphonic cantatas, symphonic poems, radio dramas, operas, ballets based on poems by Ivan Frank. The special attention of Ivan Franko to Ukrainian folklore is noted.